The vascular effects of hydrogen sulphide - White, Benjamin J. O. (2012)
In recent years it has become apparent that hydrogen sulphide (H2S) is an important biological mediator. In the vasculature, it produces complex responses: contraction in some blood vessels, relaxation in others, via multiple mechanisms. This thesis examined the relationship between H2S and oxygen in determining vascular responsiveness, and was conducted using porcine splenic and mesenteric arteries. Studies were also conducted using porcine splenic veins, since few studies have examined venous function. Additionally, studies were extended to the resistance vasculature by determining responses to a H2S donor in small arteries isolated from the rat mesentery.